El diccionari valencià-castellà inèdit de Tomàs Font i Piris - Picazo i Jover, Antoni (Caplletra. Revista Internacional de Filologia, 2015)
The unpublished Diccionari valencià-castellà by Tomàs Font i Piris is one of the most interesting works of lexicography produced during the 19th century, not only because of its richness (it compiles more than 10.000 entries), but also due to the fact that the words listed offer a rich and representative sample of the Catalan vocabulary used in this linguistic area.